The Microfinance Promise - Morduch, Jonathan (Journal of Economic Literature, 1999)
In the past decade, microfinance programs have demonstrated that it is possible to lend to low-income households while maintaining high repayment rates—even without requiring collateral. The programs promise a revolution in approaches to alleviating poverty and spreading financial services, and millions of poor households are served globally. A growing body of economic theory demonstrates how new contractual forms offer a key to microfinance success—particularly the use of group-lending contracts with joint liability. For the most part, however, high repayment rates have not translated into profits, and studies of impacts on poverty yield a mixed picture. In describing emerging tensions, the paper highlights the diversity of innovative mechanisms beyond group-lending contracts, the measurement of financial sustainability, the estimation of economic and social impacts, the costs and benefits of subsidization, and the potential to reduce poverty through savings programs rather than just credit. The promise of microfinance has pushed far ahead of the evidence, and an agenda is put forward for addressing critical empirical gaps and sharpening the terms of policy discussion.